Environmental Awareness of Secondary School Students with the Influence of Emotional Intelligence: Exploring the Link Between Emotional Intelligence and Environmental Awareness in Secondary School Students (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Emotional intelligence is divided into four categories. Awareness, Acceptance, Attitude, andAction are the four components. Emotions are aorganicprocedure taking place in the figure and brain, andthey remain not necessarily reasonable. Awareness is knowing what one feels. It entails being able toexperience a feeling without passing judgement on it. Attitudes are a type of belief that is linked toemotion. When a feeling follows or is coloured by an attitude, these are the times to be aware of. Thefeeling will last to be felt in the similar direction unless the attitude is challenged. The behaviour taken asa result of emotion and attitude is referred to as action. Educational issues in the age of globalisationneed us to change in step with the times, as the country's future development and success is dependenton the education system, leadership, instructors, and students. The age of transition marks thebeginning of adolescence. It has a significant impact on the development of a potential individual. It is atransitional period between childhood and adulthood. Some even claim that adolescence is a time ofturmoil and stress. It demands tremendous attention and concern as a period of fast changes in manyparts of an individual's life, including physical, social, emotional, and psychological. It is a formaloperational stage in which a teenager begins hypothetico-deductive reasoning, according to Piaget.They look into the reasons for each emotion. While huge attempts are made to meet bodily cravings,many people's psychic selves remain deranged. It is a time of development and maturation. The periodof adolescence is a time of adjustment to one's parents, peers, teachers, and society. Adolescents areneither entirely developed nor willing to accept adult help. As a result, they struggle to manage theiremotions. Emotional intelligence is required for people to be able to control and manage their emotions.